Optimization of a heat‐tolerant β‐glucosidase production by Bacillus sp. ZJ1308 and its purification and characterization. (28th August 2015) - Xu, Zhenni; Zhang, Lei; Yu, Ping
Abstract: Response surface methodology was used to optimize the medium composition to improve the production of the heat‐tolerant β‐glucosidase from Bacillus sp. ZJ1308. Three significant factors were found to be corn cob, beef extract, and MnSO4 ·H2 O. The final medium compositions optimized were corn cob (51.8 g/L), beef extract (23.8 g/L), salicin (0.5 g/L), MnSO4 ·H2 O (0.363 g/L), MgSO4 ·7H2 O (0.4 g/L), and NaCl (5 g/L). Under the optimal conditions, the activity of β‐glucosidase was up to 4.71 U/mL. β‐Glucosidase was purified to homogeneity with a recovery rate of 5% and a specific activity of 110.47 U/mg. The optimal pH and temperature were 7.0 and 60 °C, respectively. β‐Glucosidase was stable within a pH range of 6.0–8.0 and showed an extremely high thermostability at 80 and 90 °C, retaining 56% and 38% of its maximal activity, respectively. Ni 2+ and Ba 2+ heavily inhibited the β‐glucosidase activity. The purified β‐glucosidase showed a high substrate specificity. The kinetic parameters revealed that it had a high catalytic efficiency toward the substrate p ‐nitrophenyl‐β‐d ‐glucopyranoside ( K cat /K m = 700). It also showed a high catalytic activity toward the natural substrate salicin. This study provides a new insight into the future development and use of β‐glucosidase from Bacillus sp. ZJ1308.